Linking Internship Experience with Teacher Candidate Self-Efficacy and Teaching Motivation: Evidence from the Asistensi Mengajar Program - Priatmoko, Sigit; Urifah, Firda Nur; Rusydiana, Alfina; Sugiri, Wiku Aji (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v9i1.3148, 2024)
Real-world learning experiences are crucial in constructivist education. Teaching Assistance is one of the programmes that offers learning through real-world experiences to teacher candidates. This study aims to explore the impact of the Teaching Assistance programme on self-efficacy and teaching motivation. Involving 40 participants from Islamic Primary School Teacher Education Study Program, this study used a descriptive quantitative method with data collected through an online questionnaire based on a 7-point Likert scale. The results of the analysis showed that the majority of respondents had moderate levels of self-efficacy and motivation. This finding indicates that the Teaching Assistance programme was effective in increasing participants' self-efficacy and motivation to pursue a career as a teacher in the future, despite variations in their levels of self-efficacy and motivation. This study also shows the need to evaluate and improve the quality of the implementation of the teaching assistance programme so that participants' self-efficacy and motivation increase. Self-efficacy and motivation are critical to their future career readiness. Limitations of the study, such as the small sample size and reliance on questionnaires, lead to recommendations for further research with a more holistic approach. Overall, this study confirms that the Teaching Assistance programme can be an effective tool in preparing prospective teachers who are competent, motivated, and confident to face the challenges of the teaching profession.